2011
DOI: 10.1177/1049909111409021
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory Grief Among Close Relatives of Patients in Hospice and Palliative Wards

Abstract: A Swedish widowhood study revealed that four out of ten widows regarded the pre-loss period more stressful than the post-loss. The present investigation of close relatives to patients dying from cancer (using interviews and the Anticipatory Grief Scale) found that preparatory grief involves much emotional stress, as intense preoccupation with the dying, longing for his/her former personality, loneliness, tearfulness, cognitive dysfunction, irritability, anger and social withdrawal, and a need to talk. Psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 24 publications
(37 reference statements)
1
31
0
4
Order By: Relevance
“…Speficially, in line with a growing body of research on the significance of pre-widowhood for mental health (Bonanno et al, 2002; Carnelley et al, 1999; Vable et al, 2015; Williams et al, 2008), the present study demonstrated that depressive symptomatology among older adults of Mexican descent increased in the years approaching the death of the spouse. Due to data limitations, we did not investigate whether elevated depressive symptomatology before the transition to widowhood could be explained by such factors suggested in the literature as the cause of spousal death, caregiver responsibilities, and low well-being related to anticipation of spousal loss (Carnelley et al, 1999; Harlow et al, 1991; Johansson & Grimby, 2012). Also, in accord with prior research (Hewitt et al, 2012; Strohschein et al, 2005; Wade & Pevalin, 2004; Wilcox et al, 2003), the findings of our study indicated that the level of depressive symptoms among older adults of Mexican descent was considerably elevated during the transition to widowhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speficially, in line with a growing body of research on the significance of pre-widowhood for mental health (Bonanno et al, 2002; Carnelley et al, 1999; Vable et al, 2015; Williams et al, 2008), the present study demonstrated that depressive symptomatology among older adults of Mexican descent increased in the years approaching the death of the spouse. Due to data limitations, we did not investigate whether elevated depressive symptomatology before the transition to widowhood could be explained by such factors suggested in the literature as the cause of spousal death, caregiver responsibilities, and low well-being related to anticipation of spousal loss (Carnelley et al, 1999; Harlow et al, 1991; Johansson & Grimby, 2012). Also, in accord with prior research (Hewitt et al, 2012; Strohschein et al, 2005; Wade & Pevalin, 2004; Wilcox et al, 2003), the findings of our study indicated that the level of depressive symptoms among older adults of Mexican descent was considerably elevated during the transition to widowhood.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies with a specific focus on the pre-widowhood period point out that individuals might report elevated depressive symptomatology already during a couple of years leading to the death of a spouse (e.g., Bonanno et al, 2002; Carnelley et al, 1999; Vable et al, 2015; Williams et al, 2008). A higher prevalence of mental health issues among individuals approaching widowhood is explained by such factors as serious illness of a spouse, caregiver burden, and anticipatory grief (Carnelley et al, 1999; Harlow, Goldberg, & Comstock, 1991; Johansson & Grimby, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…This status has been conceptualised as a psychological mechanism characterised by emotional stress, intense pre-occupation with the dying, longing for his/her former personality, loneliness, fearfulness, irritability, anger and social withdrawal (Johansson & Grimby, 2012). There are evidence that in anticipatory grief some of the symptoms can be similar to a normal grief (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…As doenças mais prevalentes relacionadas ao luto antecipatório encontradas nos estudos foram: em primeiro, o câncer (Al-Gamal & Long, 2010;Al-Gamal, Long & Livesley, 2009;Anngela-Cole & Busch, 2011;Burton, Haley, Small, Finley, Dillinger & Schonwetter, 2008;Cheng, Lo, Chan, Kwan & Woo, 2010;Grassi, 2007;Gross et al, 2012;Hottensen, 2010;Jenholt Nolbris, Enska & Hellstrom, 2014;Johansson & Grimby, 2012;Johansson, Sundh, Wijk & Grimby, 2013;Liu & Lai, 2006;Mystakidou et al, 2005;Olson, 2014;Peteet, Maypal & Rokni, 2010;Pusa, Persson & Sundin, 2012;Santos & Cardoso, 2013;Sutherland, 2009); em segundo, as disfunções cognitivas (Burton et al, 2008;Chan, Livingston, Jones & Sampson, 2013;Fowler, Hansen, Barnato & Garand, 2013;Frank, 2008;Garand et al, 2012;Holley & Mast, 2009;Johansson, Sundh, Wijk & Grimby, 2013); em terceiro, a paralisia cerebral (Al-Gamal, 2013;Al-Gamal & Long, 2014) e o quadro de prematuridade (Valizadeh, Zamanzadeh & Rahim, 2013;Zamanzadeh, Valizadeh & Rahim, 2013); por fim, em quarto, um artigo sobre anomalia congênita do aparelho cardíaco (Bennett, Dutcher & Snyders, 2011) e um sobre crise psicogênica não-epilética associada ao luto antecipatório (Kaufman, 2009).…”
Section: Métodounclassified